Políticas públicas implementadas pelo Ministério Público capixaba em relação à violência de gênero contra as mulheres (2006 - 2016) - Gazele, Catarina Cecin (2021)
This paper aims to examine the preventive and extrajudicial activity for the gender violence against women that has been fulfilled by the state of Santo’s prosecutors and attorneys, covering both the metropolitan region and the countryside. It was analyzed projects from the Public Ministry’s initiative, and its actions in partnership with public entities, private companies and social movements. Actions to prevent the gender violence were treated methodologically, in their quantitative and qualitative aspects. The actions to prevent it follows the guidelines of Law nº 11.340, of August 7, 2006 – the Maria da Penha Law. To this end, this study sought knowledge to understand what and how, in the face of statistics on the gender violence theme, the Public Ministry acted within the law ten years’ frame. It was analyzed also the administrative acts that have triggered activities to prevent gender violence since 2006. In a chronological order, projects and actions were examined. It was confirmed the hypotheses put forward: that the high rate of violent gender crime is due to the persistence of patriarchy in our society, inherited from European colonization and consolidated in speeches, including religious ones, which have strength to position women as submissive even nowadays. Also, it was observed that the promotion of gender public policies with information to women about their rights, and how to seek them, how to get out of the cycle of violence, how to deconstruct the common sense of internalization that violence in conjugality is natural, breaks women’s silence, reducing cases and preventing recidivism. Moreover, more, it was confirmed that he training of military and civilian police officers and prosecutors and judges and their advisers on the Maria da Penha Law, in multidisciplinary studies, leads these agents to understand women in situations of violence as people who have their rights. It was found that public policies must have a continuous, repetitive character in order to change the patriarchal culture still in force. Key words: Gender violence; Patriarchy; Public Ministry; Public politics.